Probiotic Mixtures Consisting of Representatives of Bacteroidetes and Selenomonadales Increase Resistance of Newly Hatched Chicks to Salmonella Enteritidis Infection - Volf, Jiri; Faldynova, Marcela; Matiasovicova, Jitka; Sebkova, Alena; Karasova, Daniela; Prikrylova, Hana; Havlickova, Hana; Rychlik, Ivan (Microorganisms, 2024)
There are extensive differences in the caecal microbiota of chicks from hatcheries and those inoculated with faecal material from adult hens. Besides differences in microbial composition, the latter chickens are highly resistant to Salmonella Enteritidis challenges, while the former are susceptible. In this study, we tested whether strains from genera Bacteroides, Megamonas, or Megasphaera can increase chicken resistance to Salmonella and Campylobacter jejuni when defined microbial mixtures consisting of these bacterial genera are administered. Mixtures consisting of different species and strains from the above-mentioned genera efficiently colonised the chicken caecum and increased chicken resistance to Salmonella by a factor of 50. The tested mixtures were even more effective in protecting chickens from Salmonella in a seeder model of infection (3-5 log reduction). The tested mixtures partially protected chickens from C. jejuni infection, though the effect was lower than that against Salmonella. The obtained data represent a first step for the development of a new type of probiotics for poultry.
Keywords: Megasphaera; Megamonas; microbiota; Bacteroides; probiotics; caecum; chicken